Economic effects of the organic-microorganism complex fertilizer (omc) supply and the fito-leafat spray on the growth and the development of cabbage and chinese lettuce grown in Dong Anh district, Hanoi city - Yen, Nguyen Thi; Tri, Le Van (Academia Journal of Biology, 2014)
The apply of the FiTo-OMC fertilizer and the spray of the FiTo-leafat preparation could supply sufficient nutrition for the growth and development of cabbage, in comparison with the traditional farmer method (dung, NPK). The cabbage’ yield has increased by 4.36 tons/ha (equivalent of 9.2%) and the vegetable had safe quality. By supplying the FiTo fertilizer the nutritive substance of soil has increased and the elution was limited. The profit was of 1,240,000 VNd/ha. The use of FiTo-OMC fertilizer 6,944 kg/ha and of FiTo-leafat 1,305 grams/ha had good effects on the growth and development of chinese lettuce and the lettuce yield has increased 33.5% (equivalent of 15,263,000 VNd/ha), compared with the control; the use of FiTo-OMC fertilizer without spraying Fito-leafat has increased 17.1% of yield (equivalent of 9,406,000 VNd/ha). The vegetable quality was safe with low and permitted NO3- content and the soil nutritive substance has increased.